Ketersediaan dan Pola Pemberian Air pada Daerah Irigasi Endikat Bengkok - Reni Andayani; Ayu Marlina (Cantilever: Jurnal Penelitian dan Kajian Bidang Teknik Sipil, 2020)
Endikat Bengkok irrigation area is located in Muara Enim with an area of 1,140 ha. The Endikat Bengkok Irrigation channel used to irrigate rice fields in four villages, namely Segamit, Siring Agung, Arimantai and Fajar Bulan, districts of Semendo Barat Ulu. The source of irrigation water is available in the Endikat Bengkok River, which is a subsidiary of the Lematang River. The purpose of this study was to analyze the water availability in the Endikat Bengkok River for the adequacy of the Endikat Bengkok Irrigation Area, and the appropriate water provision group. Primary data was collected in the form of the planting group, secondary data in the form of rainfall data and climatological data. The calculation of evapotranspiration used the Penman method and the calculation of water availability used the F.J. Mock. From the calculation of water availability, it is shown that the maximum value occurred in April amounted to 48.15 m3 / s and the minimum value occurred in October amounted to 2.23 m3 / s. The availability of water for irrigation (80% dependable flow) is not sufficient to irrigate the entire Endikat Bengkok Irrigation Area. The most suitable water supply group by rotating based on the provisions of the irrigation planning criteria.